Shear zone patterns and strain distribution at the scale of a Penninic nappe: the Suretta nappe (Eastern Swiss Alps) - Marquer, Didier; Challandes, Nathalie; Baudin, Thierry (My University, 1996)
Shear zone patterns within the Suretta nappe of the Swiss Alps are studied in order to understand finite strain and bulk tectonic displacements. The Suretta nappe is chosen for two main reasons; the availability of late Variscan granites deformed during Alpine tectonics only, and because of continuous outcrop from bottom to top of the nappe.
This Alpine nappe recorded two major ductile deformation phases, which developed under low-grade metamorphic conditions. The analysis of shear zone patterns in the Roffna granite reveals that the first deformation is well developed in the entire nappe; the second deformation, however, is more localized in the lower and upper parts. The bulk asymmetry of the shear zone patterns confirms the kinematics recorded by other Penninic nappes in this area: first a stacking of the nappe towards the NW, followed by the top to the E shearing during post-thickening extensional tectonics. The shear zone patterns and strain distribution allow us to deduce kinematics at the nappe scale.